2023
DOI: 10.1002/hbm.26486
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and theta band activity share information relevant to proactive and reactive control during conflict‐modulated response inhibition

Charlotte Pscherer,
Paul Wendiggensen,
Moritz Mückschel
et al.

Abstract: Response inhibition is an important instance of cognitive control and can be complicated by perceptual conflict. The neurophysiological mechanisms underlying these processes are still not understood. Especially the relationship between neural processes directly preceding cognitive control (proactive control) and processes underlying cognitive control (reactive control) has not been examined although there should be close links. In the current study, we investigate these aspects in a sample of N = 50 healthy ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Second, theta-and alpha-band stimuli may impair response inhibition. Although studies have suggested that theta and alpha band share and transmit information to regulate conflict during response inhibition [91], not only is response inhibition involved during a task, other processes, such as error monitoring and sustained attention, are also associated with consistently reduced theta activity in the medial-frontal cortex [92,93]. Studies with anxious individuals have shown that highly anxious individuals exhibit impaired response inhibition and greater alpha activity during response control task performance [94].…”
Section: Discussionmentioning
confidence: 99%
“…Second, theta-and alpha-band stimuli may impair response inhibition. Although studies have suggested that theta and alpha band share and transmit information to regulate conflict during response inhibition [91], not only is response inhibition involved during a task, other processes, such as error monitoring and sustained attention, are also associated with consistently reduced theta activity in the medial-frontal cortex [92,93]. Studies with anxious individuals have shown that highly anxious individuals exhibit impaired response inhibition and greater alpha activity during response control task performance [94].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our hypothesis, we observed greater theta synchronization between 100 and 200 ms post-stimulus onset in the prefrontal electrode cluster in the ARHL group compared to NH controls. Theta synchronization in frontal regions has been linked to proactive and reactive control ( Cooper et al, 2015 ; Messel et al, 2021 ; Pscherer et al, 2023 ). Proactive control allows one to adapt thoughts and behavior in anticipation of task goals, including any interference, whereas reactive control is a correction mechanism that involves detection and resolution of interference after its onset ( Braver, 2012 ; Stuphorn and Emeric, 2012 ; Botvinick and Braver, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the frequency domain, modulations of theta power (Harper et al, 2014; Messel et al, 2021), alpha power (Albares et al, 2014) and beta power (DeLaRosa et al, 2020; Picazio et al, 2014) over frontal and central regions have been reported during Go/NoGo and Stop Signal tasks. While these activities were initially considered mainly in association with reactive inhibition, they are also modulated in protocols emphasizing proactive inhibition (Albares et al, 2014; Messel et al, 2021; Pscherer et al, 2023; Soh et al, 2021). These activities were associated with activations of the pre-supplementary motor area (pre-SMA), the inferior frontal cortex, and the basal ganglia (for review, see Aron, 2011; Swann et al, 2009; Swann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%